'Real people in real places': Conceptualizing power for emancipatory security through Tahrir. (June 2015) - Bilgic, Ali
The objective of emancipatory security theory is to examine the insecurities of individuals and social groups that stem from oppressive power processes, relations, and structures. However, the image of power in emancipatory security studies does not correspond to such a normative and analytical motivation. This renders the theory susceptible to substantial criticism on the grounds of inadequate analysis of resisting individuals as agents of security in their own localities. To address this issue, the present article conceptualizes 'emancipatory power'. In this exercise, Hannah Arendt's understanding of power, enriched by Judith Butler's concept of performativity and feminist insights, will be used as the theoretical foundation to tailor collective power based on trust in a 'moment' of emancipation. Collective power will be illustrated by references to the protests in Cairo's Tahrir Square in 2011.